The United Nations Security Council in the age of human rights - Genser, Jared; Stagno Ugarte, Bruno (Cambridge University Press, 2014)
"The United Nations Security Council in the Age of Human Rights is the first comprehensive look at the human-rights dimensions of the work of the only body within the United Nations system capable of compelling action by its member states. Known popularly for its failure to prevent mass atrocities in Rwanda, the former Yugoslavia, and Syria, the breadth and depth of the Security Council's work on human rights in recent decades is much broader"--